Asynchronous gossip-based data propagation protocol - Andrew, Priyanka; Antonios, Imad (Digital Information and Communication Technology and Its Applications, 2015)
Data dissemination protocols govern interaction and exchange of data among nodes in a distributed system. An understanding of data transfer protocols provides insight into efficient middleware management. Due to their simplicity, scalability and fault-tolerance, gossip-based protocols are researched widely as an effective communication strategy. The Shuffle protocol presented in [1], is an example of a decentralized, gossip-based data transfer protocol used to spread information in a wireless network via probabilistic exchange of data. This paper presents, an asynchronous variant of the Shuffle protocol and a system model that captures variability in data transmission times. This transmission time variability is inherent in dynamic networks, where such algorithms are typically deployed. A simulation-based analysis of the protocol's performance behavior is presented. Results show the effects of transmission variability, on data replication and its coverage. Also examined is the relationship between available storage and the performance of the protocol, expressed using measures such as propagation time and work. © 2015 IEEE.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Data communication systems; Data dissemination; Data dissemination protocols; Data propagation protocols; Data transfer; Data transfer protocols; Digital storage; Distributed database systems; Effective communication; Fault tolerance; Fault tolerant computer systems; Gossip-based algorithms; Gossip-based protocol; Internet protocols; Middleware; Shuffle protocol; Simulation-based analysis; Wireless networks; asynchronous gossip-based algorithm; data dissemination; data transfer protocol; dept.csc; wireless network